Influence of driving posture and driving velocity on wind drag while traveling on flat land and a downward slope in the wheelchair marathon - Akashi, K.; Yamanobe, K.; Shirasaki, K.; Miyazaki, Y.; Mitsui, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The purpose of this study was to clarify the influence of wind drag and the importance of reducing wind drag while traveling over flat ground or down a slope in the wheelchair marathon. Three wheelchair athletes were measured for FD (wind drag) while moving themselves in a wheelchair in a wind tunnel, and SD (drag area) was calculated from FD. The athletes took 4 positions (Position 1: inclining the trunk and gripping the handlebar, Position 2: inclining the trunk and reaching the arm backward, Position 3: raising the trunk and gripping the top dead point of the hand rim, Position 4: inclining the trunk and the bottom dead point of the hand rim) for the measurement, and the relationships between posture and SD were investigated. Calculated SD was used for estimation of differences in the required power according to the changes in velocity and simulation of driving on a down slope. Position 1 had the smallest SD (0.155 ± 0.010 m2) and Position 3 had the largest (0.320 ± 0.021 m2). As Position 3 also had largest sitting height and trunk incline angle, it was considered that the raised trunk posture was subject to wind drag because of the increased forward projection area. Using SD and PT (total power required to maintain a certain velocity), PD (power required to overcome FD when driving at a certain velocity) was estimated. It was clarified that when athletes drive at a velocity faster than the win time of the wheelchair marathon men`s T54 in the Paralympic Games, PT was at least 145.2 W and PD accounted for at least 60% of PT. Thus, the simulation of driving on the down slope (gradient: 2.5% distance: 200 m and initial velocity: 8.27 m/s) revealed that Position 1 reached 9.00 m/s and Position 4 reached 8.15 m/s at the end of the slope. When Position 1 reached the end of the slope, Position 4 was located 11 m behind Position 1. Therefore, Position 1 is more advantageous than Position 4 in terms of both velocity and distance.